Stability of $n$-th Order Flett's Points and Lagrange's Points - Pawlikowska, Iwona (Sarajevo Journal of Mathematics, 2024)
In this article we show the stability of Flett's points and Lagrange's points in the sense of Hyers and Ulam. 2000 Mathematics Subject Classification. 39B82, 26A24, 26A06